Biocatalysed olefin reduction of 3-alkylidene oxindoles by baker's yeast. Issue 31 (3rd August 2017) - Rossetti, Arianna; Sacchetti, Alessandro; Bonfanti, Marta; Roda, Gabriella; Rainoldi, Giulia; Silvani, Alessandra
Abstract: 3-Substituted oxindoles are very interesting molecules both for their potential biological activity and for their role as starting materials toward more complex oxindole-based structures. These molecules can be prepared by the reduction of a 3-ylidene oxindole precursor by classical metal-catalysed chemical reductions of the olefin. In this work we present a biocatalytic approach for the reduction of oxindole-based olefins using baker's yeast. All the substrates were efficiently reduced in high yields. When an α, β-unsaturated ketone was used, the corresponding saturated alcohol was obtained in high yield and ee. To further investigate the enzyme-substrate interactions a molecular docking study was also performed. Graphical abstract: